The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/00042192-200512010-00011
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled trial on the effects of soy protein containing isoflavones on quality of life in postmenopausal women

Abstract: Objective: Postmenopausal estrogen decline is implicated in several age-related physical and psychological changes in women, including decreases in perceived quality of life (QoL). A number of trials with hormone therapy showed beneficial effects of the intervention on parameters of quality of life. However, because of known or suspected serious side-effects of conventional hormone therapy there is a need for alternatives.Design: We conducted a double-blind randomized placebo-controlled trial with soy protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…We find those who sought help for climacteric symptoms through traditional Chinese medicine reported more physical and psychological problems than the reference group, but none of the 21 most frequent complaints were related to the items on general health in the WHOQOL. Following adjustment for the major determinants, none of the existing vasomotor symptoms, including hot flushes and night sweating, were related to quality of life, which is largely consistent with the findings of a number of prior studies 4,25 , including clinical trials [26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 84%
“…We find those who sought help for climacteric symptoms through traditional Chinese medicine reported more physical and psychological problems than the reference group, but none of the 21 most frequent complaints were related to the items on general health in the WHOQOL. Following adjustment for the major determinants, none of the existing vasomotor symptoms, including hot flushes and night sweating, were related to quality of life, which is largely consistent with the findings of a number of prior studies 4,25 , including clinical trials [26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 84%
“…For the present study, we made use of data from a double-blind, randomized, placebo-controlled trial that was initiated to study the effect of soy consumption on bone mineral density, cardiovascular disease, cognitive function, performances in daily life, and well being (16)(17)(18)(19). Detailed information about the study is given elsewhere (17).…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiology studies concluded Asian women, who consumed soy, experience lesser menopausal symptoms compared to Western women [9][10][11][12][13]. Soybean possesses Daidzein, one form of isoflavone substance.…”
Section: Introductionmentioning
confidence: 99%